Confidence And Practice Of Teaching Arabic In Specific Professional Standards/ Ø§Ù„Ù…Ø¹ØªÙ‚Ø¯Ø§Øª Ø§Ù„ØªØ¯Ø±ÙŠØ³ÙŠØ© ÙˆÙ…Ù…Ø§Ø±Ø³Ø§Øª Ù„Ù„ØªØ¯Ø±ÙŠØ³ ÙÙŠ Ø¶ÙˆØ¡ Ø§Ù„Ù…Ø¹Ø§ÙŠÙŠØ± Ø§Ù„Ù…Ù‡Ù†ÙŠØ© Ø§Ù„ØªØ®ØµØµÙŠØ© - AlBedayr, Jawaher (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
This study aimed to explore the teaching beliefs of Arabic teachers and their practice of teaching elementary pupils in the light of specialized professional standards in the context of virtual classes. To achieve the data, the researcher used semi-restricted interviews and structured observations with participants selected by the